AN ANALYSIS OF REFERENCE IN A SPEECH OF GRETA THUNBERG - Arni Sukmiarni; Fitria Dwi Hastuti (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The study entitled An Analysis of refrences in The Greta Thunberg Speech is aimed to identify types of references and the references mostly used in A Speech of Greta Thunberg conveyed in the National Assembly in Paris, on 23rd July 2019.. The identification of references refrences is based on the theory of Halliday and Hasan (1976). The descriptive qualitative method was employed in this study. The data were taken from the speech of Greta Thunberg and then they were identified into exophoric and endophoric references. The result showed that there are sixty-seven exophoric references, forty-six anaphoric references, and twelve cataphoric references and the mostly used refrence is exophoric reference.